FREQUENCY OF COMPLICATIONS OF TRANSFORAMINAL LUMBAR INTERBODY FUSION (TLIF): A MULTI-CENTER EXPERIENCE - Sardar Sohail Afsar; Muhammad Gulzar Khan; Yaqoob Ur Rehman (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: The transforaminal lumbar interbody fusion (TLIF) technique has become increasingly popular since its introduction by Harms in 1982. Its forerunner, posterior lumbar interbody fusion (PLIF) is limited to levels L3 to S1 since excessive retraction on the thecal sac at higher levels risks damage to the neurological structures.Objective: To determine the frequency of Complications of Transforaminal Lumbar Interbody Fusion (TLIF).Methodology: This study was multi-centre retrospective study carried out at the Department of Orthopedics and Spine Surgery, Qazi Hussain Ahmed Medical Complex, Nowshera and other private medical centers in Peshawar Pakistan. The study duration was one year from August 2021 to August 2022. A thorough evaluation of hospital records of these patients was done in terms of both intraoperative and postoperative complications. All the data was compiled and entered into SPSS version 23 for analysis.Results: In this a total of 180 patients were included. The male patients in our study were 54(30%) whereas the female patients were 126 (70%). The mean age (±SD) was 457 (±7) years with minimum age of 20 years and maximum age of 75 years. The overall rate of complications in our study was 54 (30%). Post operative ileus in our study was observed in 13 (7.22%) patients. Post operative infection in our study was noted in 12 (6.67%) patients while per operative dural tear observed in our study was 8(4.44%) patients. Implants related complications were noted in 11(6.11%) patients. Pseudoarthrosis was documented in 4(2.22%) patients. There were no cases of pulmonary embolism or DVT formation in our series.Conclusion: Transforaminal lumbar interbody fusion (TLIF) is a safe and effective option to achieve fusion in various conditions. It is technically challenging and the surgeon needs to be proficient in the technique to avoid catastrophic complications. Clinical scoring proved that our patients did benefit significantly when looking at pain and overall state of health.